The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1991
DOI: 10.1063/1.349797
|View full text |Cite
|
Sign up to set email alerts
|

A 3-dimensional model for low-pressure chemical-vapor-deposition step coverage in trenches and circular vias

Abstract: A general analytical model has been developed to calculate particle transport and spatial step coverage evolution within 2-dimensional and 3-dimensional microelectronic device structures during low-pressure chemical vapor deposition. The model can account for spatially dependent nonunity reactive ‘‘sticking probabilities,’’ anisotropic source fluxes, and trench ‘‘shadowing’’ effects. There is no restriction on the initial and evolving shape of the structure. Model results are compared to direct Monte Carlo sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…This process can induce a local averaging of the solid angles, improving the conformity. Nevertheless, several studies [31]- [35] previously demonstrated that the influence of the surface diffusion on the conformity is very low in most cases.…”
Section: Elements Of Conformity Theorymentioning
confidence: 98%
“…This process can induce a local averaging of the solid angles, improving the conformity. Nevertheless, several studies [31]- [35] previously demonstrated that the influence of the surface diffusion on the conformity is very low in most cases.…”
Section: Elements Of Conformity Theorymentioning
confidence: 98%
“…Most notable is the assumption of an equilibrium gas distribution that results in Eqs. (5) and (6) that we use above. In spite of this, the method is able to give correct results in many different cases and in particular it has been verified at high Knudsen numbers [1,17] where gas particle velocity distributions may deviate significantly from the equilibrium distribution.…”
Section: Chemistry Modelmentioning
confidence: 99%
“…For a finite triangle size, the matrix elements Tij are given as an integral, which cannot be solved analytically. Therefore, in cases where equation (3) and the procedure for the calculation of . 6.Qij lead to a significant error, the corresponding triangles i and j are each subdivided into smaller triangles.…”
Section: D Implementation Of the Cvd Modelmentioning
confidence: 99%